Awake craniotomy for operative treatment of brain gliomas - experience from University Medical Centre Ljubljana - Žele, Tilen (Radiology and oncology (Ljubljana), 2023)
Background. Awake craniotomy is a neurosurgical technique that allows neurophysiological testing with patient cooperation during the resection of brain tumour in regional anaesthesia. This allows identification of vital functional (i.e. eloquent) brain areas during surgery and avoidance of their injury. The aim of the study was to present clinical experience with awake craniotomy for the treatment of gliomas at the University Medical Centre Ljubljana from 2015 to 2019.Patients and methods. Awake craniotomy was considered in patients with a gliomas near or within the language brain areas, in all cases of insular lesions and selected patients with lesions near or within primary motor brain cortex. Each patient was assessed before and after surgery.Results. During the 5-year period, 24 awake craniotomies were performed (18 male and 6 female patients; average age 41). The patient’s cooperation, discomfort and perceived pain assessed during the awake craniotomy were in majority of the cases excellent, slight, and moderate, respectively. After surgery, mild neurological worsening was observed in 13% (3/24) of patients. Gross total resection, in cases of malignant gliomas, was feasible in 60% (6/10) and in cases of low-grade gliomas in 29% (4/14). The surgery did not have important negative impact on functional status or quality of life as assessed by Karnofsky score and Short-Form 36 health survey, respectively (p > 0.05). Conclusions. The results suggest that awake craniotomy for treatment of gliomas is feasible and safe neurosurgical technique. The proper selection of patients, preoperative preparation with planning, and cooperation of medical team members are necessary for best treatment outcome.
Keywords: awake craniotomy; clinical experiences; intraoperative neurophysiological testing; intraoperativno nevrofiziološko testiranje; kirurgija gliomov; kraniotomija v budnem stanju klinične izkušnje; primarni možganski tumorji; primary brain tumours; surgery of gliomas